Discrepancies between red cell phenotyping and genotyping for characterization of the Duffy blood system in blood donors in southern Brazil - Soares, Scheila da Silva; Deconte, Desireé; de Oliveira, Tiago Bittencourt; Almeida, Silvana; Fiegenbaum, Marilu (Revista de Ciências Médicas e Biológicas, 2024)
Abstract Introduction: Genetic variants in the ACKR1 (FY) gene, which encode Duffy red blood cell antigens, may result in weakened expression of antigens or null phenotype. Genetic variants are the main reason that led to discrepancies between phenotype and genotype. Molecular methods are a tool for the limitations of hemagglutination assays. Objective: In this study, we investigated discrepant results between serology and molecular tests for the Duffy system in blood donors from a blood center in the northwest region of Rio Grande do Sul, Brazil. Methodology: we studied 80 blood donor samples by serological method, real-time PCR, and gene sequencing. Results: of these 80 samples phenotyped for Fya and Fyb antigens and genotyped for SNPs rs12075 (c.125G>A) and rs2814778 (c.- 67T>C), 3 (3.75%) discordant samples were observed. Considering these results, the estimated kappa value for the genotype-phenotype agreement was 0.936 (95% CI 0.865-1.000). We identified an SNP c.265C>T (rs34599082) in one of the samples. We did not identify variants in the other two samples: one of them phenotyped as Fy(a+b-), and the other had phenotype Fy(a-b+). Both were genotyped as FY*A/FY*B genotype, respectively; these samples should express the Fyb and Fya antigens. Conclusion: genotyping of SNPs rs12075 and rs2814778 were concordant and showed that genotyping and phenotyping are essential to ensure 100% accuracy for Duffy blood group assignments. Sequencing is an important tool for resolving phenotype/genotype conflicts, identifying alleles that carry mutations that lead to weak expression or silencers, and identifying new variants. Keywords: Duffy blood group genotyping; discrepancies phenotype-genotype; serological testing; real-time PCR.